The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/oere-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

The polymer converter for effectively connecting polymer with silica optical fibres

Abstract: We present a micrometer−size polymer converter (microbridge)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Manufacturing of an optical fiber microtip based on the photopolymerization process was previously described many times [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 36 ]. In Figure 1 , the sketch (a) and the image (b) of the manufacturing set-up were presented.…”
Section: Microtip Manufacturing and Sensor Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Manufacturing of an optical fiber microtip based on the photopolymerization process was previously described many times [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 36 ]. In Figure 1 , the sketch (a) and the image (b) of the manufacturing set-up were presented.…”
Section: Microtip Manufacturing and Sensor Preparationmentioning
confidence: 99%
“…Previous studies have shown the possibility to fabricate the microtips on various optical fibers (i.e., SMFs [ 22 , 23 , 25 , 26 ], photonic crystal [ 24 ] and multi-mode fiber (MMF) made with silica [ 27 ] and plastic [ 25 ]). The most important applications of such micro-optical element are in scanning optical microscopes (SOM) [ 28 ], optical fibers interconnections [ 29 , 30 , 31 ], optical fiber couplers/splitters [ 32 ], VCESEL illumination profile controllers [ 33 ], and sensors [ 34 , 35 , 36 ]. In the first application, the SMF was applied to achieve a submicron resolution of the designed optical fiber-based SOM [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common methods of applying these functional materials to optical fibers is by forming an external coating after polishing the fiber [ 13 ] or fabricating a taper [ 14 , 15 , 16 ], or by filling the internal air holes in a photonic crystal fiber [ 17 ]. It is also possible to fabricate new microstructures at the end of the fiber—e.g., polymer microtips or microlenses [ 18 , 19 ]—and between two fibers of the same type or of two different types [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feasibility of the polymer microelement manufactured at the end of an optical fiber was previously demonstrated in microscopy [1], as well as fiber to fiber connector technology [2]. The author's research has shown the possibility to shape the geometry of such microstructures by using selected types of optical fibers, chemical compounds, and by tuning parameters of the photopolymerization process [3].…”
Section: Introductionmentioning
confidence: 99%